Polygynous family structure and child undernutrition in Africa: Empirical evidence from Nigeria - Amare, Mulubrhan (International Food Policy Research Institute, 2018)
Presented by Mulubrhan Amare (IFPRI), as part of the Annual Gender Scientific Conference hosted by the CGIAR Collaborative Platform for Gender Research, Addis Ababa, 25-27 September 2018.